1989
DOI: 10.1210/jcem-68-2-301
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Aberrations in Women With Functional Hypothalamic Amenorrhea*

Abstract: To further elucidate the neuroendocrine regulation of anterior pituitary function in women with functional hypothalamic amenorrhea (FHA), we measured serum LH, FSH, cortisol, GH, PRL, TSH concentrations simultaneously at frequent intervals for 24 h in 10 women with FHA and in 10 normal women in the early follicular phase (NC). Using the same data, we separately analyzed the cortisol-PRL responses to meals in these women. In addition, the pituitary responses to the simultaneous administration of GnRH, CRH, GHRH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
164
0
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(176 citation statements)
references
References 32 publications
10
164
0
2
Order By: Relevance
“…Interactions between the HPA and HPG axes in FMS patients have yet to be thoroughly investigated. However, stress has been shown to compromise fertility (35,36). In women, stressrelated increases in cortisol secretion suppress hypothalamic gonadotropin-releasing hormone (GnRH) input to the pituitary-ovarian axis.…”
Section: Neuroendocrine Function Segmentmentioning
confidence: 99%
“…Interactions between the HPA and HPG axes in FMS patients have yet to be thoroughly investigated. However, stress has been shown to compromise fertility (35,36). In women, stressrelated increases in cortisol secretion suppress hypothalamic gonadotropin-releasing hormone (GnRH) input to the pituitary-ovarian axis.…”
Section: Neuroendocrine Function Segmentmentioning
confidence: 99%
“…The 8-hour sampling period was chosen since Berga et al (8) demonstrated significant differences in LH area under the curve between normal women and women with hypothalamic amenorrhea during an 8-hour period in the afternoon and evening.…”
Section: Discussionmentioning
confidence: 99%
“…The LH pulse characteristics for each subject were analyzed by means of the computerized algorithm cluster analysis of Veldhuis and Johnson (7). Pulse characteristics such as amplitude, interpeak interval, mean peak duration, area under the curve, and peak and valley frequencies were determined (8). Rhythm was defined as the standard deviation of the interpeak intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Grande parte dos estudos que abordam o assunto enfoca particularmente as amenorréias hipotalâmicas. Sabe-se que essa situação caracteriza-se por disfunção global, reflexo da ativação do eixo hipotálamo-hipófise-adrenal e associada a aumento no tônus opióide, depressão da função tireoideana, concentrações reduzidas de leptina e de alopregnanolona (metabólito da progesterona), além de alteração na atividade inibitória do sistema receptor de GABA (Suh et al, 1988;Berga et al, 1989;Laatikainen, 1991;Berga, 1996;Dominguez et al, 1997).…”
Section: Aspectos Psíquicos E Anormalidades Menstruais: Mecanismos Fiunclassified